Citius, Altius, Fortius: beneficial effects of resistance training for young athletes: Narrative review - Faigenbaum, A. D.; Lloyd, R. S.; MacDonald, J.; Myer, G. D. (British Journal of Sports Medicine, 2016)
The motto of the Olympic Games is Citius, Altius, Fortius which is Latin for `Faster, Higher, Stronger`. It is a clarion call to all competitors, including the youngest, to engage in training strategies that prepare athletes to be the best in the world. Existing research indicates that various forms of resistance training can elicit performance improvements in young athletes. Stronger young athletes will be better prepared to learn complex movements, master sport tactics, and sustain the demands of training and competition. An integrative training programme grounded in resistance training and motor skill development can optimise a young athlete's potential to maximise their athletic and sporting performance, while reducing the risk of a sports-related injury. Resistance training may be especially important for modern-day young athletes who are more likely to specialise in one sport at an early age at the expense of enhancing general physical fitness and learning diversified sport skills. Structured interventions that include qualified instruction; targeted movement practice; and strength and conditioning activities that are developmentally appropriate, progressive and technique driven are needed to attain a level of athleticism that is consistent with the Olympic motto.